The Umm et-Grib rock-shelter and the exploitation of resources in Jebel Gharbi - Conati Barbaro, Cecilia (Libya Antiqua, 1995)
Keywords: Géologie -- Djebel Nefousa

The significance of the occurrence of Abu Ghaylan and Kiklah Formations east of Wadi Ghan, eastern Jabal Nfusah - Fatmi, A. N.; Sbeta, Ali (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie -- Djebel Nefousa

Some geochemical aspects of Al Aziziyah Formation, Jabal Nafusah - Ben Ashour, A. M.; Zaied, A.; Bakush, M. (The geology of Libya. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Keywords: Géologie -- Djebel Nefousa

The geology of Libya: Third Symposium on the Geology of Libya - Salem, M. J.; Hammuda, O. S. (Elsevier, 1991)
Keywords: Géologie -- Djebel Nefousa

Geochemical position of the Jabal Nafusah phonolites - Bausch, W. M.; Meduna, J. U. (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie -- Djebel Nefousa

Geomorphology and sedimentology in the Ghan and Zargha Wadis and on the Jado Plateau - Giraudi, Carlo (Libya Antiqua, 1995)
Keywords: Géologie -- Djebel Nefousa

Evaporite, carbonate, and siliciclastic transitions in the Jurassic sequences of southeastern Tunisia - Ben Ismail, Mohamed Hédi; M'Rabet, Ali (Sedimentary Geology, 1990)
Evaporite, carbonate and siliciclastic transitions occur within the Jurassic deposits of southeastern Tunisia. These facies are grouped into four major transgressive-regressive sequences corresponding to various environments of deposition. The latter include sabkha, subaqueous evaporite basin, carbonate tidal flats to shallow marine platform, bioherms and mixed siliciclastic ramp. Rapid lateral and vertical variations in thicknesses and facies are controlled by tectonic, climatic and eustatic factors. East-west and NW-SE fault systems generated a down-faulted graben (Tataouine basin) bordered by two uplifted horsts (Tebaga Mole and Libyan Craton) and have acted as an evaporite depocenter or as a siliciclastic trap. Eustatic-related transgressions occurring during Late Lias, Bajocian, Early/Middle Callovian, and probable Upper Callovian-Oxfordian have led to opening and/or deepening of the marine basin accompanied by carbonate sedimentation rapidly replacing evaporite or siliciclastic deposition. This Jurassic example not only confirms that tectonics and, to a lesser extent, climate largely controlled evaporite, carbonate, and siliciclastic transitions; it also demonstrates that sea-level changes may be another factor controlling such transitions in these ancient deposits.
Keywords: Géologie -- Djebel Nefousa